Perkembangan Kritik Sastra Arab Pada Masa Kontemporer: Faktor Kemakmuran, Metode Kritik, dan Kritikus - Latifa, Zuhra; Tasnimah, Tatik Mariyatut; Burhani, Muhammad Iwan (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Abstract: The development of literary criticism in the Arab world has gone through a long process, where some methods also changed and developed along with the development of literary works in the Arab world. Not much different from the world of Arabic literature which has been echoed since the jahiliyah era, since that time also literary criticism began to surface. In the realm of Arabic literary criticism, classical literary criticism is the root that exerts an influence on contemporary literary criticism. The popularity of Arabic poetry became a stimulus for the birth of criticism to the point of giving birth to several figures with their own styles of criticism. This article aims to provide a glimpse into the journey of literary criticism in the contemporary period, by presenting some of the figures who struggled and were directly involved in the develoment process of contemporary literary criticism.Keywords: Contemporary, Literary, Criticism, Arabic